Degradable packaging film and preparation method thereof
By using the combination of PLA and PBAT and curcumin, a degradable packaging film with fresh preservation, antibacterial and antioxidant functions was prepared, which solved the problem of difficult degradation and preparation of existing citrus fruit cover materials, and achieved efficient citrus fresh preservation and environmentally friendly packaging solutions.
Patent Information
- Application Number
- CN202510069431.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
The existing citrus fruit cover materials are difficult to degrade, and the antibacterial membrane prepared using PLA and PBAT is complex in preparation and has many raw materials, so the antibacterial performance needs to be further improved.
Polylactic acid (PLA) and polybutylene adipate-terephthalate (PBAT) were used as raw materials, and curcumin was added to prepare a packaging film with fresh preservation, antibacterial and antioxidant functions through mixing, extrusion and film blowing.
The prepared packaging film has good tensile properties, transparency and antibacterial effects, which can effectively extend the shelf life of citrus, and has simple process and few raw materials, which has good market prospects.
Smart Images

Figure CN119875166A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a degradable packaging film and a preparation method thereof, belonging to the technical field of food packaging. Background Art
[0002] Citrus is the most widely produced fruit in the world, distributed in about 140 countries. However, citrus is susceptible to fungal infection during storage and transportation, leading to rot and deterioration, resulting in a total yield loss rate of 30-40%. Among them, mold infection poses the most serious threat to citrus, accounting for 90% of the total post-harvest decay. Therefore, the prevention and control of pathogenic microorganisms and spoilage microorganisms on the surface of citrus needs to be solved urgently. Single fruit bagging is a commonly used method for storing citrus, and the most commonly used polyethylene, polyvinyl chloride, and polypropylene bagging packaging materials are difficult to degrade in the natural environment, causing significant harm to the earth's ecological environment, food safety, and animal health. Therefore, biodegradable plastic packaging materials can be selected to replace plastic products. Biodegradable polymers can be degraded by microorganisms into carbon dioxide and water, and eventually become part of the natural carbon cycle. Since the functional performance of biodegradable packaging materials made of a single substance is often limited, extensive research has been conducted on the development and testing of composite materials.
[0003] Polylactic acid is a polyester formed by the polymerization of lactic acid, also known as polylactide. Polylactic acid plastic prepared by the reaction of polylactic acid is a polymer material with very good degradation ability, biocompatibility and absorbency. Polylactic acid is biodegradable. It can be degraded into water, carbon dioxide and other small molecules under composting conditions, re-enter the cycle of the ecosystem, and exert less pressure on the environment. In addition, due to its unique characteristics of biocompatibility, thermoplastic processing and eco-friendliness, it has great potential for application in packaging films. However, in practical applications, polylactic acid has defects such as poor gas barrier, poor toughness and slow degradation. If you want to make good use of polylactic acid, you need to modify it. Blending modification is one of the simple and economical modification methods. Blending PLA with polybutylene adipate-terephthalate terephthalate (PBAT) can greatly improve the elongation of the film.
[0004] At present, the technology of PLA and PBAT molding in the prior art is patent CN 106751568 B, which discloses that an antibacterial PBAT / PLA composite film is prepared by adding an antibacterial compatibilizer and tetrabutyl titanate to a PBAT / PLA blend system. However, tetrabutyl titanate is a low-toxic raw material, and there are certain safety issues when used to prepare thin films.
[0005] Patent CN 119144029 A discloses a biodegradable and environmentally friendly food cling film and its manufacturing method. The food cling film is made of polybutylene adipate / terephthalate as a base material, polylactic acid composite and biological antibacterial agent as auxiliary materials, and is made through mixing, extrusion and film blowing processes. However, the method of the patent has complicated steps and many types of raw materials. Although the final product has good strength and antibacterial effect, the steps or raw material usage can be simplified in the application of food packaging to achieve a more economical and practical effect. Summary of the invention
[0006] Technical issues
[0007] The use of fruit covers plays an important role in fruit storage, but the commonly used materials of fruit covers such as polyethylene, polyvinyl chloride, and polypropylene are difficult to degrade. The use of PLA and PBAT can produce a degradable film with good physical strength, but its antibacterial performance still needs to be improved. At the same time, the technology related to antibacterial PBAT / PLA film in the existing technology generally has the problems of complex preparation and the use of multiple raw materials.
[0008] Technical content
[0009] The invention provides a degradable fresh-keeping and antibacterial packaging film and a preparation method thereof. The method uses polylactic acid (PLA) and polybutylene adipate-terephthalate terephthalate (PBAT) as raw materials, and under the action of curcumin, prepares a packaging film with fresh-keeping, antibacterial and antioxidant functions, which has a certain fresh-keeping effect on citrus and prolongs its shelf life.
[0010] Curcumin is a medicinal material, a permitted food additive, and a natural food pigment and natural food preservative. In addition, curcumin has good photosensitivity, is safe and non-toxic, and can be activated by 400-475nm blue light to produce reactive oxygen. Due to its natural source and low price, it is considered to be a photosensitizer with broad application prospects. It can produce reactive oxygen to inhibit the function of subcellular structures, produce cytotoxic effects, and ultimately lead to the death of organisms, thereby achieving antibacterial effects.
[0011] The first object of the present invention is to provide a method for preparing a degradable fresh-keeping, antibacterial and antioxidant packaging film, the preparation method comprising the following steps:
[0012] (1) mixing PLA, PBAT and curcumin uniformly to obtain a mixed material;
[0013] (2) placing the mixed material into a hopper of a twin-screw extruder, running the machine to obtain a molten material, and cutting the molten material after cooling to obtain a modified masterbatch;
[0014] (3) The modified masterbatch is stirred and dissolved in an organic solvent to obtain a film-forming liquid, the film-forming liquid is poured into a mold, and dried until the organic solvent is completely evaporated to obtain a degradable, fresh-keeping, antibacterial and antioxidant packaging film.
[0015] Furthermore, in step (1), the mass ratio of PLA to PBAT is 1:3-5.
[0016] Specifically, in step (1), the mass ratio of PLA to PBAT is 1:3.
[0017] Furthermore, in step (1), the mass ratio of PLA to curcumin is 3:0.5-1.
[0018] Specifically, in step (1), the mass ratio of PLA to curcumin is 3:0.5.
[0019] Furthermore, the average particle size of the modified masterbatch in step (2) is 1 to 2 mm.
[0020] Furthermore, in step (3), the organic solvent includes dichloromethane or anhydrous ethanol.
[0021] Furthermore, in step (3), the stirring speed is 100 to 500 rpm; and the stirring time is 12 to 48 hours.
[0022] Furthermore, in step (3), the ratio of the volume of the organic solvent to the mass of the modified masterbatch is 50-100 mL:4 g.
[0023] Furthermore, the thickness of the degradable fresh-keeping, antibacterial and antioxidant packaging film in step (3) is 0.03 to 0.06 mm.
[0024] Furthermore, the drying in step (3) includes natural air drying or heating and drying; the temperature of heating and drying is 30 to 50°C.
[0025] The second object of the present invention is to provide a degradable fresh-keeping and antibacterial packaging film prepared by the above method.
[0026] The third object of the present invention is to provide the use of the above-mentioned degradable fresh-keeping and antibacterial packaging film in fruit packaging.
[0027] Beneficial effects of the present invention:
[0028] (1) The degradable fresh-keeping, antibacterial and antioxidant packaging film obtained by the present invention has a degradable function and has little pressure on the environment; at the same time, it has good tensile properties and transparency, can be well applied to fruit bags, and does not hinder the observation of the appearance of the fruit; and through the application of citrus, it is confirmed that the packaging film can play a good fresh-keeping and antibacterial role, and has a positive effect on the water loss rate, CI color, hardness and other indicators of citrus, effectively extending the shelf life of citrus.
[0029] (2) The preparation process of the present invention is simple, uses less raw materials, and the obtained packaging film has excellent effect. It is a method with extremely practical value and suitable for promotion, and has good market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a flow chart of the preparation process of the degradable packaging film.
[0031] Figure 2 This is a graph showing the relationship between colony count and time.
[0032] Figure 3 This is a relationship diagram of DPPH free radical scavenging activity.
[0033] Figure 4 This is a diagram showing the relationship between the ABTS free radical scavenging activity.
[0034] Figure 5 This is a graph showing the relationship between the release rate of curcumin.
[0035] Figure 6 This is a curve chart of the weight loss rate of citrus at different times.
[0036] Figure 7 This is a curve chart of the change in citrus hardness at different times.
[0037] Figure 8 This is the chromaticity change curve of citrus CI at different times.
[0038] Fig. 9 It is an infrared spectrum. DETAILED DESCRIPTION
[0039] The present invention will be further described below by means of specific examples, but the protection scope of the present invention is not limited thereto.
[0040] In the following examples, the degradable packaging film may also be a film; the PLA film is the degradable packaging film prepared in Example 1; the PBAT film is the degradable packaging film prepared in Example 7; 0.25% curcumin refers to the concentration of curcumin in Example 8; 0.5% curcumin refers to the concentration of curcumin in Example 9, 0.75% curcumin refers to the concentration of curcumin in Example 10; 1.0% curcumin refers to the concentration of curcumin in Example 11.
[0041] Source of raw materials
[0042] Polylactic acid (DP 800) was purchased from a common commercial product; polybutylene adipate-terephthalate terephthalate (DP 300) was purchased from a common commercial product; phosphate buffered saline (PBS), dichloromethane, and curcumin (Cur) were purchased from Bio-Tech Biotechnology Co., Ltd. (Shanghai, China).
[0043] Examples 1 to 11
[0044] (1) Raw materials (see Table 1) are weighed and mixed according to different ratios, and the mixed raw materials are placed in the hopper of a twin-screw extruder. After the feeder is running, the raw materials slowly enter the single screw from the hopper and melt after passing through the single screw. Then, the molten material is extruded through the twin screw. After the extrudate is cooled, it is cut to obtain a modified masterbatch.
[0045] (2) Dry the modified masterbatch in step (1) to obtain a dry masterbatch, then take 4 g of the dry masterbatch and dissolve it in dichloromethane, stir it with a magnetic stirrer at room temperature overnight, and then perform ultrasonic treatment to expel bubbles.
[0046] (3) pouring the mixed solution after ultrasonic treatment in step (2) onto a stainless steel plate, casting it naturally into a film, and drying it at 20-25° C., and peeling off the film after the solvent is completely evaporated to obtain a degradable packaging film.
[0047] Table 1
[0048] Group Polylactic acid(g) PBAT(g) Dichloromethane (mL) Curcumin(mg / mL) Example 1 12 0 100 0 Example 2 10 2 100 0 Example 3 9 3 100 0 Example 4 6 6 100 0 Example 5 3 9 100 0 Example 6 2 10 100 0 Example 7 0 12 100 0 Example 8 3 9 100 0.25 Example 9 3 9 100 0.5 Example 10 3 9 100 0.75 Embodiment 11 3 9 100 1.0
[0049] The thickness of the degradable and environmentally friendly polylactic acid composite film prepared in Examples 1 to 11 is between 0.036 and 0.063 mm, and the water vapor transmission rate is between 607.4 and 988.5 g·m -2 ·s -1 between.
[0050] Example 12
[0051] The degradable packaging films prepared in Examples 1 to 11 were tested, and the test steps and results are described as follows:
[0052] 1. Evaluation of mechanical properties and barrier properties of films
[0053] Nine locations of the film were randomly selected to test the mechanical properties of the film. The tensile strength (TS) and elongation at break (EAB) of the film were measured by a dual-column benchtop test system 5967X (Instron, USA). The film samples were cut into rectangular strips (20mm×5mm) and clamped on the fixture at an initial distance of 10mm. The test was carried out at a speed of 5mm / min until the film broke. At least 7 tensile tests were performed on each film formulation at room temperature to obtain the average value.
[0054] The water vapor permeability (WVP) of the composite membrane was measured using a water vapor permeation test system. Specifically, 10 mL of ultrapure water was placed in a round ceramic cup, the membrane was fixed on the round ceramic cup, the lid was tightened, and the cups were placed in the vacuum chamber of the test system in sequence according to the serial number. The cups were circulated for 18 hours in sequence, and each group was measured 6 times to obtain the average value. The oxygen permeability (OP) of the membrane was measured. The centrifuge tube mouth containing 3.0 g of deoxidizer (reduced iron powder: sodium chloride: activated carbon = 0.5:1.5:1.0) was sealed with a membrane, and then placed in a dryer containing distilled water, and the tube weight was weighed every 24 hours for 7 consecutive days. The OP calculation method is shown in the formula:
[0055]
[0056] Where: Δm is the weight gain of the centrifuge tube, g; t is the equilibrium time, s; A is the membrane area exposed to oxygen transfer, m 2 .
[0057] Table 2
[0058]
[0059] It can be seen from Table 2 that when PLA:PBAT=1:3, 1:5, the tensile strength and elongation at break of the obtained film are both excellent. The addition of Cur slightly reduces the tensile strength of the film (p<0.05), but the elongation at break is improved, indicating that the composite film can increase the adhesion between the film components through the hydrogen bond combination with Cur, thereby increasing the force required to break the film.
[0060] For the film doped with Cur, the water vapor permeability of the film decreased, which may be because curcumin, as a hydrophobic substance, reduced the invasion of water molecules. At the same time, the oxygen permeability (p < 0.05) also decreased, which may be because the antioxidant effect of curcumin absorbed more oxygen, or it may be that the curcumin particles reduced the pore size of the membrane and reduced the penetration of oxygen molecules.
[0061] 2. Color evaluation standards
[0062] The color and optical properties of the film were measured. The sample surface color was measured with a standard white plate (L*=96.37, a*=-0.27, b*=0.35) as the background. The color parameters L* (brightness), a* (green / red) and b* (blue / yellow) were measured. Next, the film was placed on a standard white plate and five readings were recorded at random points on each film. The parameters measured were a*, b* and L*. The total color difference (ΔE) was calculated as follows:
[0063]
[0064] Table 3
[0065] Group L* a* b* ΔE* Example 1 91.37±0.32a -0.69±0.01a -1.11±0.15c 75.32±0.11c Example 2 90.35±0.45b -0.85±0.37c -1.35±0.28b 73.72±0.70b Example 3 90.57±0.21a -0.65±0.05a -1.25±0.17c 74.28±0.15c Example 4 90.22±0.11a -0.73±0.18a -1.18±0.21c 75.66±0.17c Example 5 91.09±0.54a -0.75±0.08a -1.13±0.13c 73.23±0.13c Example 6 90.12±0.37a -0.89±0.04a -1.22±0.16c 78.21±0.22c Example 7 90.19±0.22c -0.77±0.41b -1.12±0.31a 72.45±0.58a Example 8 87.39±0.65b -9.85±0.07c 88.35±5.48b 113.72±4.70b Example 9 85.09±0.02c -2.07±0.40b 113.02±0.69a 132.45±0.58a Example 10 77.39±0.34b -1.85±0.16c 118.23±1.28b 143.12±0.70b Embodiment 11 75.09±0.09c -1.07±0.32b 134.02±1.09a 152.03±0.45a
[0066] As can be seen from Table 3, the incorporation of curcumin significantly affected the L*, a*, b* and ΔE* values of the PLA / PBAT film compared to the blank film (p < 0.05). The results of the luminescence parameter (L*) showed that the L* value of the film with the addition of curcumin was lower than that of the other blank films, indicating the loss of white brightness due to the bright orange color of curcumin; the a* parameter of all films showed negative values, which indicated a tendency towards green, proving that the yellow color of the film loaded with curcumin crystals was stronger, and the 0.5% curcumin PLA / PBAT film had a deeper yellow color than the 0.25% curcumin PLA / PBAT film; b* showed a positive value indicating that the color of the film tended to be yellow, and for the two films containing curcumin, the ΔE* value showed the same behavior; compared with the control film, a significant increase in the b* value was observed with the increase in the concentration of curcumin, indicating that the yellow color of the film increased. According to the color, the PLA / PBAT film with the addition of curcumin has a bright yellow color and good transparency, which is suitable for packaging fresh products such as citrus.
[0067] 3. UV analysis
[0068] The UV-vis absorption spectrum of the film was measured using an ultraviolet spectrophotometer. The film was cut into rectangles (1.0 cm × 5.0 cm) and placed in a quartz cuvette, and the transmittance of the film sample (10 × 40 mm) was measured at 280 and 660 nm wavelengths using air as a reference, and the transmittance at 280 nm (T280) and 660 nm (T660) was used to evaluate the UV blocking performance and transparency of the film.
[0069] Table 4
[0070]
[0071]
[0072] As can be seen from Table 4, the result of T660 (5.0%) shows that the PBAT film is translucent, and the addition of PLA can significantly improve the transparency of the PBAT film. At the same time, the addition of Cur will have a certain impact on the transparency of the film, but overall, the films obtained in Examples 8 to 11 are transparent. Therefore, in the case of excellent tensile properties, the transparency of Examples 5 and 9 is more in line with practical applications.
[0073] 4. Antimicrobial activity
[0074] The antibacterial activity of the Cur film prepared in Examples 8 to 11 against foodborne pathogens Listeria monocytogenes and Salmonella Typhimurium was determined by the live colony counting method. First, the strain was inoculated into LB broth under a sterile environment, and then incubated overnight at 37°C on a shaker to obtain the target bacterial solution (108-109 CFU / mL). The film was cut into samples of 1×1 cm in size, placed in a sterile culture medium, and 50 μL of diluted bacterial solution (105-106 CFU / mL) was dripped onto the film, and the light was irradiated for 0 min, 30 min, 60 min and 120 min respectively, and then the bacterial solution on the film was washed off with PBS, and the plate was smeared on the culture medium to observe the colony count.
[0075] The results are as follows Figure 2 As shown in the figure, Cur film has a significant inhibitory effect on foodborne pathogens Salmonella and Listeria monocytogenes. The bacterial concentration is reduced by 3.5log CFU / mL by the conversion of colony count, and the inhibitory effect can reach 99.9%. The antibacterial activity of 0.5% and 1.0% Cur film is significantly higher than that of 0.25% film, while 0.5% and 1.0% Cur film show considerable antibacterial activity. Preferably, 0.5% concentration of curcumin film can meet our antibacterial needs.
[0076] 5. Antioxidant Activity
[0077] Antioxidant activity The antioxidant activity of the Cur films prepared in Examples 8 to 11 was evaluated using DPPH· and ABTS·+ free radical scavenging activity, and the film obtained in Example 5 was taken as a control. For the DPPH assay of the curcumin film, a predetermined amount of the film was added to 10 mL of DPPH solution, and the absorbance at 517 nm was measured after 24 hours. For the ABTS analysis, a predetermined amount of the test film was mixed with 10 mL of ABTS assay solution, and the absorbance at 734 nm was measured after 24 hours. The antioxidant activity of the film was calculated using equation (4):
[0078]
[0079] Among them, A0 and A T The absorbance of DPPH or ABTS for the control and test membranes, respectively. All experiments were repeated three times and the average values were reported.
[0080] The results are as follows Figure 3 and 4As shown, since curcumin is a well-known antioxidant, the film with curcumin is also expected to show antioxidant activity, and the activity depends on the content of curcumin. The scavenging rates of pure PBAT / PLA film for DPPH and ABTS are 44% and 70%, respectively. When the curcumin content is 0.5%, the scavenging rates of the film for DPPH and ABTS are increased to 75% and 98%, respectively, which are comparable to the antioxidant activity of the film with a high concentration of curcumin. Preferably, the curcumin concentration of 0.5% is the optimal ratio.
[0081] 6. Curcumin release test
[0082] The amount of curcumin put into water from the Cur films prepared in Examples 8 to 11 was determined. The test film samples (2.5 cm×2.5 cm) were transferred into 20 mL of distilled water and incubated at 37° C. 2 mL of the solution samples were collected at predetermined intervals and the absorbance of the samples at 420 nm was measured.
[0083] The results are as follows Figure 5 As shown, the release rate of curcumin is related to the concentration of curcumin. For high curcumin content (1.0%), the amount of released curcumin increases linearly with the soaking time.
[0084] 7. Test on the preservation performance of citrus
[0085] The citrus fruits purchased from the market are first selected for suitable size and uniform color, packaged with film, and stored at room temperature. The weight loss rate, hardness and CI color of the samples are measured on the 0th day, 1st day, 3rd day, 5th day, and 7th day respectively.
[0086] Determination of fruit weight loss rate: The weight loss rate of citrus during storage reflects the loss of water. Figure 6 It can be seen that with the increase of storage time, the weight of citrus gradually decreases and the volume of the fruit gradually decreases. Adding 0.5% Cur film can effectively inhibit the respiration of citrus, reduce the loss of nutrients, effectively inhibit the growth of microorganisms, effectively maintain the freshness of citrus, and improve the appearance of citrus.
[0087] Determination of fruit firmness: Figure 7 This is a curve of the hardness change of citrus at different times. During storage, the respiration rate of citrus gradually increases, which also increases the water loss of citrus to a certain extent, and the water loss is closely related to the reduction of hardness. By measuring the hardness index of each citrus, it was found that with the increase of storage time, the hardness of each group gradually decreased. The hardness of citrus treated with 0.5% Cur film was higher than that of other groups, which confirmed the water retention function of 0.5% Cur film.
[0088] Determination of fruit color: Figure 8This is a graph showing the chromaticity change of citrus at different times. By comparison, the color of citrus wrapped with 0.5% Cur film is obviously brighter, the citrus has a good color, and there are no obvious wrinkles; while the color of citrus in other groups has lost its color, the surface of the citrus is dull, and even appears gray-brown. The barrier performance of adding 0.5% Cur film effectively reduces the respiration of citrus, reduces the aggregation of microorganisms on the surface of citrus, reduces the loss of citrus quality, and maintains the color; in addition, 0.5% Cur film does not have a negative impact on the surface color of citrus, and there is no fading, pollution, etc., which has a color protection effect on citrus.
[0089] 8. Infrared spectrum test
[0090] FTIR spectrometer at 4000-400 cm -1 The FTIR spectrum of the Cur film was obtained in the spectral range of .
[0091] Fig. 9 The FTIR spectrum of the film is shown in Figure 2. The PBAT / PLA film has a peak at 2946 cm -1 The absorption peaks at 1715 cm-1 correspond to the OH stretching vibration and the CH stretching vibration. -1 C=O stretching vibration peak, 723cm -1 It is the -(CH2)4 vibration peak, which only exists when there are 4 or more CH2 groups on a chain. The stretching vibration of the CO bond is at 1300-1050cm -1 The peak is at 1253cm -1 The characteristic peak at 2946cm corresponds to the stretching vibration of aromatic CO. The absorption peak of -CH- asymmetric stretching vibration is at 2946cm -1 , the absorption peak of in-plane bending vibration of -CH(CH3) is 1451cm -1 By observing the spectrum, it was found that after adding the active substance, there was only a slight difference in the spectrum. This should be because the active substance was only physically mixed with the material, and neither new functional groups nor new substances were formed, which had almost no effect on the infrared spectrum of the film.
[0092] 9. Hydrophilicity test
[0093] The hydrophilicity / hydrophobicity of a material can usually be evaluated by water absorption, which reflects the hydrophilicity / hydrophobicity of the surface or internal body of the material over a longer period of time. Cut the film into a size of (2×2cm), weigh the initial weight of the film m0, then dry it in a drying oven at 105°C for 24 hours, and finally weigh m1. The dried film is then immersed in 30mL of ultrapure water for 24 hours (25°C) and weighed m2. The membrane in ultrapure water needs to be dried again in an oven at 105°C for 24 hours and weighed m3. Five samples are used for each treatment to measure the water content (WC), solubility (SD) and swelling rate (WS). WC, SD, and WS are then calculated as follows:
[0094]
[0095]
[0096]
[0097] Table 5
[0098]
[0099]
[0100] As can be seen from Table 5, the addition of Cur significantly changed the water content of the film (p<0.05). This is due to the hydrophobicity of Cur. The composite film enhanced with Cur can reduce the water content and surface drying. This phenomenon may be due to the formation of a dense membrane network after ion enhancement, which hinders the contact between some hydrophilic groups and water molecules and weakens the water capture ability of the Cur film. The water solubility of the Cur film is lower than that of the control film, indicating that the water resistance of the film has been improved. The decrease in the water solubility of the film after adding Cur is due to the hydrophobicity of Cur. Cur can improve the cohesion of the membrane matrix and act as a physical barrier to prevent water molecules from entering the membrane. The film containing Cur contains many hydroxyl groups, which can easily combine with more water, resulting in high swelling. The swelling rate of the 0.5% Cur film is the highest, while the swelling rate of the film without Cur is generally low. The addition of Cur significantly increases the swelling rate of the film. The solubility and swelling rate of the film in water reflect the integrity of the film in a high-moisture environment. Low water solubility and mild swelling are basic requirements for film application.
[0101] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a degradable, fresh-keeping, antibacterial and antioxidant packaging film, characterized in that: The preparation method comprises the following steps: (1) mixing PLA, PBAT and curcumin uniformly to obtain a mixed material; (2) placing the mixed material into a hopper of a twin-screw extruder, running the machine to obtain a molten material, and cutting the molten material after cooling to obtain a modified masterbatch; (3) stirring and dissolving the modified masterbatch in an organic solvent to obtain a film-forming liquid, pouring the film-forming liquid into a mold, and drying until the organic solvent is completely volatilized to obtain a degradable, fresh-keeping, antibacterial, and antioxidant packaging film; In step (1), the mass ratio of PLA to PBAT is 1:3-5, and the mass ratio of PLA to curcumin is 3:0.5-1.
2. The preparation method according to claim 1, characterized in that The mass ratio of PLA to PBAT in step (1) is 1:
3.
3. The preparation method according to claim 1, characterized in that: The mass ratio of PLA to curcumin in step (1) is 3:0.
5.
4. The preparation method according to claim 1, characterized in that: The average particle size of the modified masterbatch in step (2) is 1 to 2 mm.
5. The preparation method according to claim 1, characterized in that: The organic solvent in step (3) includes dichloromethane or anhydrous ethanol.
6. The preparation method according to claim 1, characterized in that: The stirring speed in step (3) is 100 to 500 rpm; the stirring time is 12 to 48 hours.
7. The preparation method according to claim 1, characterized in that: In step (3), the ratio of the volume of the organic solvent to the mass of the modified masterbatch is 50-100 mL:4 g.
8. The preparation method according to claim 1, characterized in that: The thickness of the degradable fresh-keeping, antibacterial and antioxidant packaging film in step (3) is 0.03 to 0.06 mm.
9. A degradable fresh-keeping and antibacterial packaging film, characterized in that: The degradable fresh-keeping and antibacterial packaging film is prepared by the preparation method described in any one of claims 1 to 8.
10. Use of the degradable fresh-keeping and antibacterial packaging film of claim 9 in fruit packaging.
Citation Information
Patent Citations
A kind of antibacterial pbat / pla composite film and preparation method thereof
CN106751568B
Biodegradable environment-friendly food preservative film and manufacturing method thereof
CN119144029A
Full-biodegradable high-barrier PLA / PBAT composite packaging film
CN112280261A
Biodegradable high-barrier-property antibacterial composite film and preparation method thereof
CN113354853A
High-toughness and high-antibacterial degradable composite film based on cellulose nanoalkene as well as preparation method and application of high-toughness and high-antibacterial degradable composite film
CN115558141A
Cited By
PBAT / PLA antioxidant composite film and preparation method thereof
CN120535923A
Composite biodegradable packaging film as well as preparation method and application thereof
CN120792282A
Antibacterial film, preparation method and freshness protection bag
CN121673624A